2015
DOI: 10.1105/tpc.15.00314
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of Microtubule Interacting Proteins over the Course of Xylem Tracheary Element Formation in Arabidopsis

Abstract: Plant vascular cells, or tracheary elements (TEs), rely on circumferential secondary cell wall thickenings to maintain sap flow. The patterns in which TE thickenings are organized vary according to the underlying microtubule bundles that guide wall deposition. To identify microtubule interacting proteins present at defined stages of TE differentiation, we exploited the synchronous differentiation of TEs in Arabidopsis thaliana suspension cultures. Quantitative proteomic analysis of microtubule pull-downs, usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
78
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(86 citation statements)
references
References 91 publications
5
78
0
3
Order By: Relevance
“…First, we confirmed that the downregulation of CSI1/POM2 caused aberrant secondary wall deposition in proto-and metaxylem trans-differentiating cell suspension cultures (Derbyshire et al, 2015;Supplemental Figures 1A and 1B). Using confocal microscopy, we quantified the occurrence of spiral, reticulate, and pitted secondary wall patterns and the percentage of calcofluor-stained irregular deposits in the secondary walls of nontransgenic and CSI1 downregulated cell lines (Supplemental Figures 1C and 1D).…”
Section: Csi1/pom2 Influences Xylem Vessel Wall Patterningsupporting
confidence: 70%
See 2 more Smart Citations
“…First, we confirmed that the downregulation of CSI1/POM2 caused aberrant secondary wall deposition in proto-and metaxylem trans-differentiating cell suspension cultures (Derbyshire et al, 2015;Supplemental Figures 1A and 1B). Using confocal microscopy, we quantified the occurrence of spiral, reticulate, and pitted secondary wall patterns and the percentage of calcofluor-stained irregular deposits in the secondary walls of nontransgenic and CSI1 downregulated cell lines (Supplemental Figures 1C and 1D).…”
Section: Csi1/pom2 Influences Xylem Vessel Wall Patterningsupporting
confidence: 70%
“…MAP65-1, AIR9, MAP70-1, and MAP70-5 (Pesquet et al, 2010;Derbyshire et al, 2015). These proteins contribute to the MTbundling/stabilization and are important to achieve the MT array rearrangements during secondary wall synthesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In these systems, non-xylem plant cells can be triggered to transdifferentiate into xylem-like cells by hormonal treatment 45,46 . Using trans-differentiation systems, xylem formation has been studied in cell cultures of Zinnia elegans [46][47][48] and Arabidopsis thaliana (Arabidopsis) 49,50 . These studies resulted in the discovery of the master regulators of proto-and metaxylem formation Vascular NAC Domain 7 (VND7) and VND6 respectively in Arabidopsis 45 .…”
Section: Transdifferentiation Systems To Study Xylem Formationmentioning
confidence: 99%
“…The discovery of transdifferentiating cell cultures, triggering non-xylem cells to develop into xylem like cells, has greatly helped to identify cellular processes involved in xylem formation. The benefits are that these transdifferentiation cells cultures can be synchronised and are well suitable for analysis by microarrays 45,48 , proteomics 50 and experimental cell biology 46,47,49,129 . Microarray analysis followed up by overexpression experiments revealed the master regulators for proto-and metaxylem formation, respectively VND7 and VND6 45 .…”
Section: Putative Molecular Components Involved In Protoxylem Patterningmentioning
confidence: 99%